2014
DOI: 10.1111/jpm.12177
|View full text |Cite
|
Sign up to set email alerts
|

The life course of women who have experienced abuse – a life chart study in general psychiatric care

Abstract: The life chart offers rich information that provides a broader picture of the lives of women who have experienced abuse. Life charts could be useful for nurses identifying women in general psychiatric care who have experienced abuse. Despite experiences of abuse and stressful events during childhood, there were only a few indications of them receiving support in the life charts. Many of the women had as adults been in contact with or received care at numerous healthcare services. Violence against women is a wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The study also showed that the women who had no experience of abuse during their childhood reported less anxiety and fear growing up (Örmon et al . ). The phenomenon of suffering is also described as a duality between caring and noncaring general psychiatric care.…”
Section: Discussion Of the Results In Relation To A Caring Science Pementioning
confidence: 97%
See 1 more Smart Citation
“…The study also showed that the women who had no experience of abuse during their childhood reported less anxiety and fear growing up (Örmon et al . ). The phenomenon of suffering is also described as a duality between caring and noncaring general psychiatric care.…”
Section: Discussion Of the Results In Relation To A Caring Science Pementioning
confidence: 97%
“…A time geographic life chart study by Örmon et al . () shows how 11 women with experiences of abuse and mental ill health reported experiences of abuse throughout their life course and with a variety of perpetrators. Even if the time geographic study also reported ‘good’ periods where the women lived their lives without stressful events or abuse, a majority of the women described their suffering as lifelong.…”
Section: Discussion Of the Results In Relation To A Caring Science Pementioning
confidence: 99%
“…In addition, men and women involved in intimate partner violence as both victims and perpetrators are negatively associated with health‐related quality of life . FV exposure as an adult is associated with a lower physical and mental health status . Women were at increased risk of physical and mental health symptoms, and men were at increased risk primarily for mental health symptoms .…”
Section: Discussionmentioning
confidence: 99%
“…The physical and mental health of victims is negatively affected by abuse and affected women may experience the chronic somatic complaints, reproductive problems, injuries (13), depression, post-traumatic stress disorder, anxiety, suicidal behavior, substance use, sleep and eating disorders, feelings of guilt, shame and of being worthless (13)(14)(15)(16)(17). The negative effects of spousal abuse are intergenerational in that maternal abuse is associated with risk for poor behavioral functioning in her child (16).…”
Section: Introductionmentioning
confidence: 99%